Environmental factors and STEM career path choice intentions of junior secondary school girls in North-Central Nigeria (2021)
The study investigated the influence of environmental factors on STEM career path choice intentions among secondary school girls in North-Central Nigeria. It was motivated by the low representation of females in STEM fields globally and particularly in Nigeria. Survey design was adopted for the research. The population comprised of 5,433 junior secondary school girls from Federal Government Colleges in the geo-political zone. The sample size was 361 girls and multi-stage sampling technique was used for the selection. The instrument for data collection was a validated questionnaire. Data were analyzed using the descriptive statistics and binary logistics regression. Findings showed that secondary school students at the junior level have high intentions to choose STEM career path. Teachers, role model and parents significantly influenced secondary school girls STEM career path choice intentions. Therefore, it is recommended that secondary school management should motivate and sustain the female students’ STEM career intentions of girls among others.